Fouling Detection in an Optically Accessible Microstructured Heat Exchanger. Issue 10 (16th July 2019) - Spiegel, Christoph; Kraut, Manfred; Rabsch, Georg; Küsters, Christof; Augustin, Wolfgang; Scholl, Stephan
Abstract: The application of highly effective microstructured devices in continuous production and industrial environments is frequently prone to fouling. A new method is presented to characterize fouling in these microstructures. Thermal fouling of aqueous solutions containing whey protein were used as a test system. Different fouling effects could be observed and distinguished. Integral fouling indicators, such as thermal fouling resistance and pressure drop, as conventional criteria for the occurrence of fouling were compared with direct local optical observation. Low thermal fouling resistances could be detected. Abstract : The use of microstructured devices in continuous processes is still challenging. This work presents an optical approach to investigate fouling and plugging phenomena in a microstructured heat exchanger. Cow milk‐based whey protein is chosen as a model system. Initial results support the general suitability of this approach.